Avaliação da qualidade do ar e as emissões atmosféricas em grandes cidades de América do Sul - Pelaez, Luisa Maria Gomez (2019)
Air pollution is the largest and most persistent environmental problem in South America and in the world. Exposure to PM2.5 is considered the largest environmental health risk. According to World Health Organization (WHO), in 2016, the 91% of the urban population lived in cities that exceed the minimum levels established by this Organization for PM2.5. This research presents a review of the long-and short-term concentrations of air pollutants such as nitrogen dioxide (NO2), Sulphur dioxide (SO2), particulate matter (PM10 and PM10), carbon monoxide (CO) and ozone (O3) recorded between 2010 and 2017 in automatic monitoring networks of eleven metropolitan regions of South America (Including 3 of 3 from 28 and 34 large mega-cities in the world). Despite efforts to monitor air quality, in some cities were found large gaps in the diffusion, consistency and presentation of information provided by the environmental authorities. In comparison with the annual WHO Air Quality Guidelines (WHO-AQG), the particulate matter (PM2.5 and PM2.5) registered in all cities, exceeded during every year of the period studied, the NO2 has been exceeded by 4 of the 11 cities that had record. The guideline of the daily average of who to SO2 was exceeded only by Vitoria (over the past two years), cities like Rio de Janeiro and Belo Horizonte, had exceedances above the Interim Target 1 (IT-1). The ozone (average running averages of 8 hours) always been below the WHO-AQG, but Rio de Janeiro, São Paulo and Belo Horizonte, had every year atypical data of exceedance the WHO-AQG and IT-1. In the emissions review was found that 6 of 11 cities has no recent inventories available, in the 5 that have no inventory was analyzed the 2012 information of Emissions Database for Global Atmospheric Research (EDGAR). The inventories found are updated in the maximum until the year 2016, which makes it more difficult for environmental authorities generate environmental policies and make effective air quality management. Most of the inventory was developed with emission factors from other cities and even other countries, but despite the fit with local conditions is necessary investment in the development of local factors which make it possible to comply with the principles of quality, transparency, accuracy, consistency, comparability and completeness.